2012
DOI: 10.1212/wnl.0b013e3182535d20
|View full text |Cite|
|
Sign up to set email alerts
|

Evidence-based guideline update: Pharmacologic treatment for episodic migraine prevention in adults

Abstract: Objective: To provide updated evidence-based recommendations for the preventive treatment of migraine headache. The clinical question addressed was: What pharmacologic therapies are proven effective for migraine prevention? Methods:The authors analyzed published studies from June 1999 to May 2009 using a structured review process to classify the evidence relative to the efficacy of various medications available in the United States for migraine prevention. Results and Recommendations:The author panel reviewed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
342
0
14

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 711 publications
(357 citation statements)
references
References 38 publications
1
342
0
14
Order By: Relevance
“…A migrénes roham mind a beteg, mind az orvos szá-mára ijesztő lehet időnként, különösen az esetleges bevezető (aura)tünetekkel járó migrén, illetőleg a heves vegetatív tünetekkel járó formák (1. táblázat). Megkü-lönböztetünk akut (roham)terápiát, amelynek célja a beteg aktuális rohamának oldása, a fájdalom, illetőleg a vegetatív tünetek csökkentése, megszüntetése; illetőleg megelőző (intervallum)terápiát, amelynek célja a migré-nes rohamok gyakoriságának és erősségének a csökken-tése (3. táblázat) [8,9,10].…”
Section: A Migrén Akut (Roham Alatti) éS Megelőző (Intervallum)kezeléseunclassified
See 2 more Smart Citations
“…A migrénes roham mind a beteg, mind az orvos szá-mára ijesztő lehet időnként, különösen az esetleges bevezető (aura)tünetekkel járó migrén, illetőleg a heves vegetatív tünetekkel járó formák (1. táblázat). Megkü-lönböztetünk akut (roham)terápiát, amelynek célja a beteg aktuális rohamának oldása, a fájdalom, illetőleg a vegetatív tünetek csökkentése, megszüntetése; illetőleg megelőző (intervallum)terápiát, amelynek célja a migré-nes rohamok gyakoriságának és erősségének a csökken-tése (3. táblázat) [8,9,10].…”
Section: A Migrén Akut (Roham Alatti) éS Megelőző (Intervallum)kezeléseunclassified
“…Nyilván-valóan nincs minden migrénes betegnek erre szüksége, hiszen a ritka, illetőleg esetlegesen enyhe tünetekkel járó formák esetén ez nem indokolt [8,9,10]. Egyértelmű ajánlás nincs, célszerű azon betegeknél ezt megfontolni, akiknek a fejfájás jelentősen rontja az életminőségét, illetőleg szignifi káns mértékű fájdalomcsillapító szedésére szorulnak, kockáztatván a fájdalomcsillapító-abúzus (és ennek súlyos következményei: gyomorvérzés, analgeticumnephropathia, csontvelő-toxicitás) és következmé-nyes provokált fejfájás (medication overuse headache) lehetőségét [7].…”
Section: A Migrén Akut (Roham Alatti) éS Megelőző (Intervallum)kezeléseunclassified
See 1 more Smart Citation
“…Silberstein et al assessed pharmacological therapies for the prevention of migraine and identified 29 Class I or Class II articles from published studies. 13 They concluded that antiepileptic drugs (divalproex sodium, sodium valproate and topiramate), β-blockers (metoprolol, propanolol and timolol) and triptans (frovatriptan for short-term menstrual migraine prevention) were effective for migraine prevention (Level A -medicines with established efficacy in at least two Class I trials). These drugs should be prescribed to patients with migraine to reduce attack frequency and severity.…”
mentioning
confidence: 99%
“…These drugs should be prescribed to patients with migraine to reduce attack frequency and severity. 13 Triptans are effective for migraine relief and their use represented a breakthrough in the treatment of migraine.…”
mentioning
confidence: 99%